1997
DOI: 10.1002/(sici)1097-4628(19970411)64:2<343::aid-app15>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Graft copolymerization of benzyl methacrylate onto wool fibers

Abstract: Benzyl methacrylate (BzMA) was graft copolymerized onto wool fibers by using ammonium peroxydisulphate as the initiator. Grafted samples with different polymer add ons (from 7 to 180%) were obtained by varying the monomer concentration in the reaction system. Following grafting with BzMA, the X-ray diffraction peak at 20.2Њ slightly moved towards higher spacing values. Birefringence decreased, indicating a lower degree of molecular orientation of grafted wool fibers. The equilibrium regain values of grafted wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 9 publications
2
37
0
Order By: Relevance
“…Different studies have shown that grafting may cause slight or severe changes in the thermal behavior of the fibers, the extent of which depends on several parameters, such as the kind of used monomer, grafting conditions and grafting percentage [5][6][7]. The results of DSC are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Different studies have shown that grafting may cause slight or severe changes in the thermal behavior of the fibers, the extent of which depends on several parameters, such as the kind of used monomer, grafting conditions and grafting percentage [5][6][7]. The results of DSC are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, silk crease recovery, dimensional stability, rub resistance, photo yellowing, oil and water repellency, color fastness, have been dramatically improved [5,6] by means of grafting. In the case of wool, the internal deposition of different polymers may change tensile properties, felting shrinkage, abrasion and pilling resistance, hygroscopicity, chemical resistance, thermal stability, dying behavior, rot resistance, durability and bacterial resistance [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have used KMnO 4 as an initiator. Tsukada et al have used ammonium peroxysulfide as an initiator to graft benzyl methacylate on wool fibres (Tsukada et al, 1997). They have also reported that the tensile strength of grafted fibres increases while elongation and breaking strength decreases.…”
Section: Wet Chemical Processingmentioning
confidence: 99%